Visible light-mediated cross-coupling of electrophiles: synthesis of α-amino amides from isocyanates and ketimines. Issue 6 (27th January 2021) - Zhu, Junli; Dai, Cancan; Ma, Mengyue; Yue, Yanni; Fan, Xinyuan
Abstract : Cross-couplings between the electrophilic ketimines and isocyanates are achieved via the visible light-mediated reactivity inversion of the ketimines, affording the desired α-amino amides in high yields, with both metal and metal-free systems. Abstract : A catalytic system to synthesize α-amino amides from isocyanates and ketimines has been developed using visible light iridium photoredox catalysis via umpolung reactivity of ketimines. Cross-couplings between diverse ketimine and isocyanate substrates have been evaluated, affording the desired α-amino amide products in good yields. In addition, a metal-free catalytic system using perylene and N, N -diisopropylethylamine has been developed. Finally, single-step synthesis of the psychoactive drug benzodiazepine-2-one analogue from one of the coupling products has been achieved, indicating the great application potential of the synthetic method developed herein.